Efforts to Improve Integrated Services Post (POSYANDU) Cadre Skills in Stunting Detection Through Cadre Training - Fitria Prabandari; Sumarni Sumarni; Suryati Suryati; Nadya Alifah Putri; Erika Erika; Septianingsih Septianingsih (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The Integrated Services Post (Posyandu) program is good enough to monitor children's growth and development, but with the Covid-19 pandemic, Posyandu activities have been temporarily suspended face-to-face, thus monitoring the development and growth of toddlers, which is usually carried out by cadres at Posyandu, is also hampered. Therefore, efforts are needed to improve the skills of Posyandu cadres to detect stunting within the scope of the Dasawisma as assistance to mothers of toddlers both online and in face-to-face meetings while still paying attention to health protocols to prevent the spread of the Covid-19 virus. The purpose of this activity is to improve the skills of Posyandu cadres in stunting detection through cadre training. The method of this activity is the preparation of coordination with partners, coordination with village midwives and cadres, determining a joint schedule, making media booklets and questionnaires, then continuing with the implementation of activities starting with pretest, training, and evaluation with posttest, and assistance for stunting detection activities. The results of this community service are that after training Posyandu cadres experienced an increase in knowledge and skills on stunting detection, as many as 26 Posyandu in Karangkelsem Village received a grant for stamping scales and height measuring devices, and the skills of Posyandu cadres in detecting stunting increased. This community service concludes that training can improve the knowledge and skills of Posyandu cadres in detecting stunting during the Covid-19 pandemic.